The double : and, the gambler - Dostoyevsky, Fyodor, 1821-1881.; Pevear, Richard, 1943-; Volokhonsky, Larissa; Dostoyevsky, Fyodor, 1821-1881. (New York : Everyman's Library, 2005)
Presents two stories, one in which Goliadkin, a minor official, becomes aware of a strange doppelganger who replaces him with his friends and associates, and another, depicting Alexei Ivanovich's obsession with gambling and troubles with women.
Double -- The gambler.
Includes bibliographical references.
Adult
Keywords: Dostoyevsky, Fyodor, -- 1821-1881 -- Translations into English; Dostoyevsky, Fyodor, -- 1821-1881.